2000
DOI: 10.1111/1469-8986.3710065
|View full text |Cite
|
Sign up to set email alerts
|

Development of multimodal attention in young infants: Modification of the startle reflex by attention

Abstract: This study examined the effect of attention engagement to compound auditory-visual stimuli on the modification of the startle blink reflex in infants. Infants at 8, 14, 20, or 26 weeks of age were presented with interesting audiovisual stimuli. After stimulus onset, at delays defined by heart rate changes known to be associated with sustained attention or attention disengagement, blink reflexes were elicited by visual or auditory stimuli. Blink amplitude to either visual or auditory stimuli was enhanced when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Due to the translational focus of this review, we will discuss only those studies that included psychophysiological data such as startle and skin conductance. The startle reflex can be measured in very young children; one study examined startle in infants from 2 to 6 months of age, and found a gradual increase in startle magnitude over that age range [61]; another study found that 5-month-old infants showed modulation of startle with emotion [62]. An affective modulation of the startle study with children from 3 to 9 years old and adults found an increase in baseline startle with age, but equivalent levels of affective modulation across all groups [63].…”
Section: Reviewmentioning
confidence: 99%
“…Due to the translational focus of this review, we will discuss only those studies that included psychophysiological data such as startle and skin conductance. The startle reflex can be measured in very young children; one study examined startle in infants from 2 to 6 months of age, and found a gradual increase in startle magnitude over that age range [61]; another study found that 5-month-old infants showed modulation of startle with emotion [62]. An affective modulation of the startle study with children from 3 to 9 years old and adults found an increase in baseline startle with age, but equivalent levels of affective modulation across all groups [63].…”
Section: Reviewmentioning
confidence: 99%
“…Two lines of reasoning suggest that attention may operate somewhat differently with complex and dynamically changing stimuli than with simple geometric patterns. First, the level of heart rate change in infants to static or dynamic geometric patterns is much smaller and less sustained than the heart rate change to stimuli with audio and visual components (Richards, 1998(Richards, , 2000Richards & Cronise, 2000;Richards & Gibson, 1997). Phasic changes in HR are thought to correspond to different levels of attention engagement (Berg & Richards, 1997;Richards, 2007Richards, , 2010Richards & Casey, 1992;Richards & Hunter, 1998).…”
mentioning
confidence: 99%
“…Excessive or reduced arousal levels are generally associated with poor performance whereas moderate levels of arousal are associated with peak performance (see also Ashton, 1971;Williams & Golenski, 1979). A large body of evidence indicates that the amount or type of available sensory stimulation can directly affect young organisms' arousal level, thereby serving to increase or decrease an infant's attention to the specific features of sensory stimulation present in the perinatal environment (for examples, see Gardner & Karmel, 1995;Richards, 2000;Ruff & Rothbart, 1996). The tight link between arousal and attention in early development likely plays an important role in young organisms' perceptual learning and development.…”
mentioning
confidence: 99%